A RADIOACTIVE WASTE REPOSITORY IN THE BORDER AREA BETWEEN THE REPUBLIC OF CROATIA AND BOSNIA AND HERZEGOVINA: HUMAN SECURITY PERSPECTIVE (Security Dialogues, 2023)
The Republic of Croatia has announced a plan to build a radioactive waste repositoryin Mount Trgovska Gora located along the border area with Bosnia and Herzegovina (BiH),which has upset residents living in the border municipalities in BiH. This paper seeks toexamine local residents’ opinion regarding the construction of a radioactive waste repository. Our study was conducted in Novi Grad, a place located in the immediate vicinity of TrgovskaGora. The aim of the study was to examine local residents’ perceptions and the implications ofthe planned project for human security. This study is based on a qualitative research approachusing the focus group interview as a technique. Eleven respondents participated in the focusgroup interview. The group consisted of representatives of local communities, residents, andrepresentatives of non-governmental organizations. Our findings indicate that local residentsstrongly disagree with the announced project and numerous negative implications for human security.
Keywords: radioactive waste, human security, ecology, sustainable development, Trgovska gora